The effects of childhood health on adult health and SES in China - James P. Smith; Yan Shen; John Strauss; Yang Zhe; Yaohui Zhao (Institute for the Study of Labor (IZA), 2010)
In this paper, we model the consequences of childhood health on adult health and socioeconomic status outcomes in China using a new sample of middle aged and older Chinese respondents. Modeled after the American Health and Retirement Survey (HRS), the CHARLS Pilot survey respondents are forty-five years and older in two quite distinct provinces - Zhejiang, a high growth industrialized province on the East Coast, and Gansu, a largely agricultural and poor province in the West. Childhood health in CHARLS relies on two measures that proxy for different dimensions of health during the childhood years. The first is a retrospective self-evaluation using a standard five-point scale (excellent, very good, good, fair, or poor) of general state of one's health when one was less than 16 years old. The second is adult height often thought to be a good measure of levels of nutrition during early childhood and the prenatal period. We relate both these childhood health measures to adult health and SES outcomes during the adult years. We find strong effects of childhood health on adult health outcomes particularly among Chinese women and strong effects on adult BMI particularly for Chinese men.
Keywords: H00; 330; childhood health; China